2020
DOI: 10.3390/catal10101182
|View full text |Cite
|
Sign up to set email alerts
|

The Characterisation of Electrodeposited MoS2 Thin Films on a Foam-Based Electrode for Hydrogen Evolution

Abstract: Molybdenum sulphide is an emerging precious-metal-free catalyst for cathodic water splitting. As its active sites catalyse the Volmer hydrogen adsorption step, it is particularly active in acidic media. This study focused on the electrochemical deposition of MoS2 on copper foam electrodes and the characterisation of their electrocatalytic properties. In addition, the electrodeposition was modified by adding a reducing agent—sodium hypophosphite—to the electrolyte. To reveal the role of hypophosphite, X-ray pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…It is worth noting that the (200) peak became the most intense after depositing a MoS 2 film on the fs-Cu, which probably shows that MoS 2 tends to deposit on the (111) plane. Moreover, an XPS analysis carried out on similarly synthesized films in a previous study confirmed the formation of Mo(IV)-S bonds [ 34 ].…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…It is worth noting that the (200) peak became the most intense after depositing a MoS 2 film on the fs-Cu, which probably shows that MoS 2 tends to deposit on the (111) plane. Moreover, an XPS analysis carried out on similarly synthesized films in a previous study confirmed the formation of Mo(IV)-S bonds [ 34 ].…”
Section: Resultsmentioning
confidence: 52%
“…Electrochemical impedance spectroscopy is a very useful tool in heterogeneous electrocatalyst characterization because it gives the ability to measure certain parameters that are related to the electrochemically active or even electrocatalytically active surface area of the electrode. In previous studies, EIS has been used to compare the electrocatalytic activities of electrodes with an uncertain geometrical surface area [ 34 , 52 ] and a similar approach was applied here. The EIS spectra were obtained at overpotentials where little to moderate hydrogen evolution occurs, depending on the catalytic activity of the electrode (−0.1 V, −0.2 V, −0.3 V).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high activity, excellent stability and precious metal-free composition of MoS 2 makes it suitable for performing sustainable and feasible HER electrocatalysis [ 16 ]. Different forms of active HER MoS 2 electrocatalysts have been developed, including crystalline nanoparticles, amorphous films and molecular clusters [ 1 , 3 , 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. MoS 2 is also characterized by unique photocatalytic properties [ 3 , 6 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%